2003
DOI: 10.1093/humrep/deg275
|View full text |Cite
|
Sign up to set email alerts
|

The effects and effectiveness of laparoscopic excision of endometriosis: a prospective study with 2-5 year follow-up

Abstract: Laparoscopic excision of endometriosis significantly reduces pain and improves quality of life for up to 5 years. The probability of requiring further surgery is 36%. Return of pain following laparoscopic excision is not always associated with clinical evidence of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(111 citation statements)
references
References 19 publications
5
105
0
1
Order By: Relevance
“…These observations agree with those of Cheong et al, 13 but not with the lower requirement of reoperation in other observations. 12,14 …”
Section: Discussionmentioning
confidence: 99%
“…These observations agree with those of Cheong et al, 13 but not with the lower requirement of reoperation in other observations. 12,14 …”
Section: Discussionmentioning
confidence: 99%
“…However, some clinical studies provide evidence that pain symptoms are reduced after surgical excision of the pEL [31,32], but still less than half of the treated women responded to the pain-reducing surgery [33,34]. However, other studies could not verify this level of chronic pelvic pain reduction after peritoneal lesion excision in endometriosis patients [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies could not verify this level of chronic pelvic pain reduction after peritoneal lesion excision in endometriosis patients [35,36]. In addition, it is reported that 40–50% of the patients experienced pain recurrence to a level that subsequent laparoscopy was performed within 2 years [32,35,37] and 20% of the patients with severe recurrent symptoms still had no visible endometriotic lesions [32]. This indicates that a reduction in pain through an excision of the visible lesion is still not fully satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has a large impact on the quality of life and is associated with extensive physical and psychological morbidity [10,11,12,13,14]. Moreover, the cost of endometriosis is a burden to society due to medical costs of treatment and economic costs because of the inability to work [11,15].…”
Section: Introductionmentioning
confidence: 99%